Whether there are different organisational culture typologies in contemporary UK universities? - Wang, Xirui (2018)
In this increasingly competitive world, business organisations are evolving, so does the educational sector. However, this change mixed with hope and fear. In 2018, a large-scale industrial action held by lecturers from many prestigious UK universities. It is a strike over pension cuts, nevertheless, what lies behind is an undergoing transformation subject to political and economic changes. This strike led to a serious question of what modern universities are and whether their culture has changed. A novel and systematic qualitative content analysis was conducted. According to the findings, there are four types of organisational culture co-exist in most UK universities; however, the balance has tilted to the entrepreneurial side. Notwithstanding the worrying situation of a public service turning into some profit-driven organisations, lecturers who involve in teaching and research still believe in the original mission of universities.